Transforaminal Blood Patch for the Treatment of Chronic Headache from Intracranial Hypotension: A Case Report and Review - Bowden, Kirk (Hindawi Publishing Corporation, 2012)
This case report describes the successful treatment of chronic headache from intracranial hypotension with bilateral transforaminal (TF) lumbar epidural blood patches (EBPs). The patient is a 65-year-old male with chronic postural headaches. He had not had a headache-free day in more than 13 years. Conservative treatment and several interlaminar epidural blood patches were previously unsuccessful. A transforaminal EBP was performed under fluoroscopic guidance. Resolution of the headache occurred within 5 minutes of the procedure. After three months without a headache the patient had a return of the postural headache. A second transforaminal EBP was performed again with almost immediate resolution. The patient remains headache-free almost six months from the time of first TF blood patch. This is the first published report of the use of transforaminal epidural blood patches for the successful treatment of a headache lasting longer than 3 months.